RESPON PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) TERHADAP PEMBERIAN FORMULA DAN TAKARAN PUPUK ORGANIK PLUS PADA STADIA TBM 1 - Supreyitno, Duwi; Syafrullah, Syafrullah; Amir, Nurbaiti (Universitas Muhammadiyah Palembang, 2017)
Growth Response of Palm Oil Plants (Elaeis guineensis Jacq) Against Giving Formula and Dose Organic Plus Fertilizer Plus At Stadia TBM 1. The aim of this research is to get the best organic fertilizer formula and dosage on the growth of oil palm crop (Elaeis guineensis Jacq) on TBM 1 stadium. This research has been done in Campus C Experimental Garden of Muhammadiyah University of Palembang, Semambu Island Village, North Indralaya Subdistrict, Ogan Ilir District, South Sumatera, from May to August 2016. The design used Factorial Factorial Factorial Random Design Factor, with 9 treatment combinations 3 replicates and 3 plant samples. (F) consisting of F1 = Humat Coal 55%, N 20% Fertilizer, P 10%, K 10%, Natural rock 5%., F2 = 60% Coal Fumed, N Fertilizer 15% , P 10%, K 10%, Natural rock 5%, F3 = Humidity 60% Coal, N fertilizer 10%, P 10%, K 10%, Natural rock 10%. Types of organic fertilizer plus (T) consist of T1 = 1 Kg / Tree, T2 = 1.5 kg / Tree, T3 = 2 Kg / Tree. The variables observed in this study were Plant High Increase (cm), Litrage Growth (cm), Length Waist (cm), and Round Quantity (multiply), Diversity analysis showed that organic fertilizer formula plus, organic fertilizer plus significant effect until very real to all observed variables. Likewise, the treatment of combinations between treatments had significant effect until very real on all observed variables, but it was not significant effect on the number of leaves / plants.